Hormonérzékeny prosztatadaganatok kezelésének új irányai [New therapeutic options for hormone sensitive prostate cancers] - Maráz Anikó; Géczi Lajos; Küronya Zsófia (2019)
During the last decades androgen deprivation therapy (ADT) was the standard treatment of prostate cancers. Survival of metastatic patients is 4 years if they receive ADT, but in case of poor prognosis survival rate is under 3 years. Since 2014 two prospective phase III studies have proven the survival advantage of early docetaxel therapy, administered together with ADT, for metastatic hormone-sensitive prostate cancer patients. Its advantage was even more considerable in case of high-volume metastatic cases. In two other studies the benefit of abiraterone-prednisone therapy combined with ADT was proven in comparison with ADT itself in case of newly diagnosed, metastatic, high-risk, hormone-naïve patients. One prospective study has proven the survival benefit of ADT administered together with radiotherapy of the prostate in case of low volume metastatic diseases. In our analysis we demonstrate these clinical studies and try to answer the contradictory questions about the occasionally overlapping therapeutic options.